2014
DOI: 10.1086/679104
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Sibling (Dis)similarity: Total Family Impact on Status Variation in the Netherlands in the Nineteenth Century

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…For 25,433 men, I can even study the influence of 9,116 great-grandfathers. An advantage of using multilevel models is that they allow studying both conventional measures of family influence (father-son and grandfather-grandson correlations) and what are often regarded as more comprehensive measures of family influence (brother and cousin correlations) (Hällsten 2014 ; Jencks et al 1972 ; Knigge et al 2014 a).…”
Section: Introductionmentioning
confidence: 99%
“…For 25,433 men, I can even study the influence of 9,116 great-grandfathers. An advantage of using multilevel models is that they allow studying both conventional measures of family influence (father-son and grandfather-grandson correlations) and what are often regarded as more comprehensive measures of family influence (brother and cousin correlations) (Hällsten 2014 ; Jencks et al 1972 ; Knigge et al 2014 a).…”
Section: Introductionmentioning
confidence: 99%
“…Homogamy increased due to marriage restrictions and, with industrialization, it increased for higher social classes. Seiler suggests that the latter might be related to the temporary increase in inequality in the early phases of industrialization, a phenomenon sometimes called the 'Great Gatsby curve' (Krueger, 2012; see also Knigge et al, 2014;Nielsen, 1994). Elites whose fortunes grew in times of rising inequality might have tried to keep their fortunes among themselves by carefully selecting elite spouses for their children.…”
Section: Some Results From This Special Issuementioning
confidence: 99%
“…Proponents of modernization theory assume an ongoing reduction in the importance of ascribed characteristicssuch as status of the family of originin favor of achieved characteristics. (Treiman, 1970; for reviews see Knigge, Maas, & van Leeuwen, 2014;van de Putte, 2005;Zijdeman & Maas, 2010). In a traditional society, the best predictor of the future earnings capacity of young adults was that of family of origin.…”
Section: A Succinct Theoretical Framework To Study Who Married Whom Amentioning
confidence: 99%
“…For instance , van Leeuwen and Maas (1997) demonstrated that in the province of Utrecht, three types of social mobility (in their terms, intergenerational, career and connubial) increased significantly in the period 1850 to 1940. Knigge et al (2014) similarly found that fathers' influence on son's occupations lessened over the course of the nineteenth century. Hastening these shifts were the nineteenth century's various demographic transitions, which were largely wrought by industrialization.…”
Section: Changing Height and Ses Dynamicsmentioning
confidence: 89%